2015
DOI: 10.1177/0145482x1510900302
|View full text |Cite
|
Sign up to set email alerts
|

Braille and Tactile Graphics: Youths with Visual Impairments Share Their Experiences

Abstract: Introduction: Data were collected from youths with visual impairment about their experiences with tactile graphics and braille materials used in mathematics and science classes. Methods: Youths answered questions and explored four tactile graphics made using different production methods. They located specific information on each graphic and shared their thoughts about the quality of the graphics. Results: Twelve youths in 6th to 12th grades participated. Almost all participants reported typically receiving bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 3 publications
2
35
0
2
Order By: Relevance
“…For both types of readers, the teachers noted the need to sometimes simplify the graphic. Their opinions align with the findings of Zebehazy and Wilton (2014c) and Rosenblum and Herzberg (2015), who each reported that although students felt positive about the quality of graphics they used, the density and complexity of some graphics posed challenges to them. It is critical for producers of both braille and print graphics to design the graphics so students can accurately and easily locate necessary information.…”
Section: Discussionsupporting
confidence: 68%
“…For both types of readers, the teachers noted the need to sometimes simplify the graphic. Their opinions align with the findings of Zebehazy and Wilton (2014c) and Rosenblum and Herzberg (2015), who each reported that although students felt positive about the quality of graphics they used, the density and complexity of some graphics posed challenges to them. It is critical for producers of both braille and print graphics to design the graphics so students can accurately and easily locate necessary information.…”
Section: Discussionsupporting
confidence: 68%
“…The results were mixed, indicating that students generally found tactile representations helpful. However, students gave examples of problems that could arise, including too little information or too much (cluttered) information, lines, and textures that are not raised enough to feel, or even materials not being ready in time for the associated classroom lesson (Rosenblum & Herzberg, 2015). This study helps reflect the need for continued research into developing and implementing high-quality tactile materials for students with VI.…”
Section: Methods For Teaching Ell Students With VImentioning
confidence: 99%
“…Given the limitations of tactile graphics and research by Bolt and Thurlow (2004) indicating that student conceptual understanding might not be indicative of their ability to read a tactile graphic, some have suggested that 3-D printing may hold the key to improving conceptual understanding for students with visual impairments (Horowitz and Schultz, 2014;Koehler et al, 2015;Rosenblum and Herzberg, 2015;Horvath and Cameron, 2016;Jo et al, 2016) and can increase STEM engagement and create accessible curriculum content (Buehler, Comrie, Hofmann, McDonald and Hurst, 2016). Stangl, Kim and Yeh (2014) reported on the use of 3-D printed picture books for young children for developing emergent literacy skills and creating a community of practice around creating and improving the process of creating these books as an instructional tool for young children.…”
Section: -Dimensional Printingmentioning
confidence: 99%
“…Researchers have suggested that 3-D printing may hold promise for students with visual impairments to address concept development, provide access to visual information (Horowitz and Schultz, 2014;Koehler et al, 2015;Rosenblum and Herzberg, 2015;Horvath and Cameron, 2016;Jo et al, 2016) and to specifically address science content (Horowitz and Schultz, 2014;Hasper et al, 2015). This article presents the results of a study on the use of 3-D printed models in a science classroom for students with visual impairments and examines whether the use of these models impacts student conceptual understanding and misconceptions related to geosciences concepts, specifically plate tectonics.…”
Section: Introductionmentioning
confidence: 99%